An empirical analysis of inflation's influence on income inequality in Lithuania - Gabija Mudričenko; Daiva Laskienė; Vilda Gižienė; Valentinas Navickas (Economics, Management and Sustainability)
Income inequality is a growing problem worldwide, especially in developed countries, with adverse social, economic, political and health consequences. In 2017, the goal of reducing poverty and inequality was included in the United Nations' seventeen Sustainable Development Goals list. Despite this, governments are not paying enough attention to tackling the problem, and inequality continues to rise. To take appropriate measures to reduce income inequality, it is essential first to understand the underlying causes, as this can help to tackle the problem at its root. Many different factors have been identified as impacting income inequality, one of which is inflation. Inflation is currently at an all-time high in the country, reaching as high as 19.7% in 2022. This makes it particularly difficult for low-income earners to make ends meet, as buying necessities is becoming harder and harder. Given that rising inflation, due to geopolitical factors, is also an issue in Lithuania and throughout Europe, it is essential to analyse the relationship between income inequality, as this can help us make the right decisions in tackling both problems. This study aims to identify the impact of inflation on income inequality in Lithuania. The research methods used to achieve the objective were graphical analysis, literature analysis, correlation analysis and regression analysis. The study shows a linear relationship between the Gini coefficient and inflation, as measured by the change in the GDP deflator, in Lithuania over 2008-2021, but that the impact of inflation on inequality is observed after one year. Similarly, a parabolic relationship is found when examining the impact of a change in inflation, as measured by the change in the GICP, on income inequality. However, changes in producer prices significantly impact income inequality only after three years. An analysis of the impact of changes in the prices of different commodities on income inequality reveals that, over the period analysed, the main contributors to inequality have been increases in the prices of oil, gas, food, and non-alcoholic beverages. Inflation directly impacts income inequality in Lithuania, so policymakers should consider it when formulating social policy.